THE INFLUENCE OF TECHNOLOGICAL CAPACITY AND FINANCIAL CAPACITY ON PROMOTING FIRM COMPETITIVENESS AND FIRM PERFORMANCE - Almashhadani, Mohammed; Almashhadani, Hasan Ahmed (Transpublika Publisher, 2023)
In today's dynamic economic landscape, businesses continually strive to enhance their competitive edge and overall performance. This study investigates the crucial roles played by technological and financial stability in a company's success and competitiveness. By analyzing a diverse range of businesses across various industries, we aim to illuminate the intricate relationship between these dimensions and their combined impact on a firm's operational effectiveness. Our comprehensive approach employs quantitative financial analysis, technology assessments, and performance metrics, supported by advanced statistical methods. Additionally, qualitative insights from expert interviews enrich our understanding. The results highlight the interdependence between technological and financial strength, underscoring their significance in boosting corporate competitiveness. A firm's capacity to capitalize on growth opportunities and navigate economic challenges is notably influenced by financial factors such as capital accessibility, liquidity, and investment strategies. Similarly, technological capacity, encompassing digital infrastructure and innovation adoption, drives operational efficiency and market distinctiveness. This research unveils the synergistic effects of harnessing both technology and financial resources, enabling strategic resource allocation that empowers businesses to sustain competitiveness, foster innovation, and adapt to evolving market dynamics. These insights hold profound implications for both theoretical research and practical management, emphasizing the need to balance investments in technical and financial capabilities. They provide valuable guidance for researchers, policymakers, and business leaders grappling with an increasingly competitive landscape. Ultimately, this study advances our comprehension of the factors shaping firm success and equips businesses with a roadmap for surmounting challenges and seizing opportunities in today's dynamic market.